The Influence of the Social Environment on the Social Care Character of Class XI Students of SMK PGRI Pekanbaru - Anggi Lestari; Jumili Arianto; Indra Primahardani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is motivated by a low sense of social concern among adolescents and even adults. This study aims to find out whether there is an influence of the social environment on the social care character of class XI students of SMK PGRI Pekanbaru which was carried out at SMK PGRI Pekanbaru, Riau. This study used the Quantitative Descriptive method, where the data collection instrument used was in the form of a questionnaire/questionnaire which had 24 statements distributed to 45 respondents. Based on the calculation results, Fcount (32.906) ˃ Ftable (4.07) is obtained which means that Ha is accepted. Based on the results of the analysis, a simple linear regression equation was obtained, namely Y = 16.507 + 0.492X, meaning that if the social environment (X) increases by 1, then the social care character (Y) increases by 0.492. So that it can be inferred from the results of the F test, there is an influence between the variable X on the variable Y, which means receiving Ha, namely: There is an Influence of the Social Environment on the Social Care Character of Class XI Students of SMK PGRI Pekanbaru.